What did I miss? In-Meeting Review using Multimodal Accelerated Instant Replay (AIR) Conferencing - Junuzovic, Sasa; Inkpen, Kori; Hegde, Rajesh; Zhang, Zhengyou; Tang, John (CHI 2011, 2011)
People sometimes miss small parts of meetings and need to quickly catch up without disrupting the rest of the meeting. We developed an Accelerated Instant Replay (AIR) Conferencing system for videoconferencing that enables users to catch up on missed content while the meeting is ongoing. AIR can replay parts of the conference using four different modalities: audio, video, conversation transcript, and shared workspace. We performed two studies to evaluate the system. The first study explored the benefit of AIR catch-up during a live meeting. The results showed that when the full videoconference was reviewed (i.e., all four modalities) at an accelerated rate, users were able to correctly recall a similar amount of information as when listening live. To better understand the benefit of full review, a follow-up study more closely examined the benefits of each of the individual modalities. The results show that users (a) preferred using audio along with any other modality to using audio alone, (b) were most confident and performed best when audio was reviewed with all other modalities, (c) compared to audio-only, had better recall of facts and explanations when reviewing audio together with the shared workspace and transcript modalities, respectively, and (d) performed similarly with audio-only and audio with video review.